Students’ perceptions of the use of phonemic charts and digital dictionaries in English Phonology Class - Diah Merrita; Ninuk Lustyantie; Syamsi Setiadi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study aims to investigate students’ perceptions of the use of digital dictionaries and phonemic charts in English phonology learning. Employing a mixed-method research design combining descriptive quantitative and qualitative approaches, the instruments used were questionnaires and semi-structured interviews. The questionnaire items were categorized into three sections: perceived usefulness (PU) consisting of four items, perceived ease of use (PEOU) consisting of three items, and behavioral intention (BI) consisting of two items. The research sample consisted of 40 first-year students of the English Education Study Program in the academic year 2025/2026 who were enrolled in the Introduction to General Linguistics course. Phonology instruction in this course was conducted over four class meetings in one semester. Simple statistical analysis was employed to analyze the quantitative data. The results indicate that students have very positive perceptions of the use of the Cambridge Advanced Learner’s Dictionary (CALD) and the Phonemic Chart application in phonology learning. Students perceive both media as useful in facilitating their understanding of phonemic symbols and improving their pronunciation skills. In terms of ease of use, the majority of respondents reported that both applications were easy to operate. Furthermore, students showed a strong intention to continue using both tools in the future. Interview findings further confirm that audio features and phonemic symbols are highly helpful, while the challenges encountered were minimal, mainly related to internet access.